2017
DOI: 10.1161/atvbaha.117.309287
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Ability of HDL From Patients With Metabolic Syndrome but Without Diabetes Mellitus to Activate eNOS

Abstract: We provide evidence that the activation of eNOS by HDL is decreased in MetS patients before the appearance of diabetes mellitus and that sphingosine-1-phosphate depletion of HDL is the main factor responsible for this defect. This has important consequences on the impairment of HDL functionality and antiatherogenic properties in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 35 publications
0
35
0
5
Order By: Relevance
“…Table 1. Compositional and functional changes of HDL in pathological conditions ACS, CAD HDL-mediated cholesterol efflux [196]; HDL-mediated NO stimulation [94]; inhibition of superoxide production [94]; antiinflammatory properties and pro-inflammatory properties [94]; endothelial repair [94]; PON1 activity [94]; inhibition of endothelial apoptosis, pro-apoptotic pathways [135]; clusterin content [135], apoC-III content [135,214]; apoA-IV, SAA and complement C3 content [213] FH HDL-C levels; HDL-mediated cholesterol efflux [197,217]; antioxidant properties [201]; anti-inflammatory activity [201,217]; TG and sphingomyelin content [216] T2DM HDL-C levels; pre-ß1 HDL [198]; ABCA1-mediated cholesterol efflux [198]; anti-inflammatory properties of apoA-I [62] and HDL [222] HF HDL inflammatory index [239]; SAA content [239]; PON1 activity [218,239] efflux capacity [200] MetS TG content [203], S1P content [203], HDL-mediated eNOS activation [203]; anti-oxidative properties [240]; anti-apoptotic activity [206]; CE and TG content [206] Premature AMI HDL inflammatory index [220]; number of large HDL particles [220] CKD HDL2 and HDL3, LCAT and HL deficiency, CETP activity, TG and PL content, antioxidant and anti-inflammatory properties, RCT [224]; NO production [225] Autoimmune disease ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1. Compositional and functional changes of HDL in pathological conditions ACS, CAD HDL-mediated cholesterol efflux [196]; HDL-mediated NO stimulation [94]; inhibition of superoxide production [94]; antiinflammatory properties and pro-inflammatory properties [94]; endothelial repair [94]; PON1 activity [94]; inhibition of endothelial apoptosis, pro-apoptotic pathways [135]; clusterin content [135], apoC-III content [135,214]; apoA-IV, SAA and complement C3 content [213] FH HDL-C levels; HDL-mediated cholesterol efflux [197,217]; antioxidant properties [201]; anti-inflammatory activity [201,217]; TG and sphingomyelin content [216] T2DM HDL-C levels; pre-ß1 HDL [198]; ABCA1-mediated cholesterol efflux [198]; anti-inflammatory properties of apoA-I [62] and HDL [222] HF HDL inflammatory index [239]; SAA content [239]; PON1 activity [218,239] efflux capacity [200] MetS TG content [203], S1P content [203], HDL-mediated eNOS activation [203]; anti-oxidative properties [240]; anti-apoptotic activity [206]; CE and TG content [206] Premature AMI HDL inflammatory index [220]; number of large HDL particles [220] CKD HDL2 and HDL3, LCAT and HL deficiency, CETP activity, TG and PL content, antioxidant and anti-inflammatory properties, RCT [224]; NO production [225] Autoimmune disease ...…”
Section: Discussionmentioning
confidence: 99%
“…. HDL modified in vitro as well as HDL isolated from patients with CAD, diabetes, metabolic syndrome, chronic kidney disease or acute coronary syndrome fail to stimulate endothelial eNOS-activating pathways and NO production [94,[202][203][204] (Table 1).…”
Section: Alterations Of Atheroprotective Properties Of Hdl In Cardiovmentioning
confidence: 99%
“…Ezetimibe did not affect the plasma concentration of high-density lipoprotein-a beneficial cholesterol with vasoprotective property of enhancing endothelial NO production through activation of eNOS. 72 Denimal et al 73 showed that this beneficial effect of high-density lipoprotein was impaired by the sphingosine-1-phosphate depletion of high-density lipoprotein in patients with metabolic syndrome. On the basis of the premise that targeting glucagon-like peptide (GLP)-1 could provide better treatment of diabetes mellitus via pleiotropic cardiovascular protective effects beyond glycemic control, many clinical trials of GLP-1-based therapies have been conducted with variable effects on cardiovascular outcomes, and others are ongoing.…”
Section: Novel Therapeutic and Diagnostic Targets Agents For Metabolimentioning
confidence: 99%
“…Localization and activity of eNOS are affected by lipid enrichment and enhanced kinetic stimulation of protein kinase C-meditated phosphorylation of eNOS at S1177. 81,82 Shear stress-induced PKC-mediated phosphorylation of endothelial eNOS at S1177 is also affected by glycolysis-dependent purine signaling and autophagy, 83 indicating that eNOS stimulation occurs via multiple mechanisms. Where eNOS and vasodilator-stimulated phosphoprotein (VASP) – a PKG target – have been genetically deleted in mice, inflammatory cytokines, monocyte adhesion and macrophage infiltration have been observed in adipose tissue.…”
Section: Reactive Nitrogen Speciesmentioning
confidence: 99%